Activated Paphia undulate Shells Waste (APSW): A Cost-Effective Catalyst for Biodiesel Synthesis from Rubber and Jatropha curcas Seeds Oil (RSOME & JSOME) - Said, N.; Fatimah A., Misebah; Siti F., Haron; Nur S., Ghazali; R. M., Yunus; Jolius, Gimbun (IACSIT Press, 2014)
Abstract—The Paphia undulata shell, which is available in abundance, has no any further processing for value-added materials and is commonly discarded as solid waste, was used as solid catalyst in a transesterification reaction to synthesize biodiesel from Rubber and Jatropha curcas seeds oil (RSOME and JSOME). The biodiesel non-vegetable oil feedstock and catalyst were prepared, characterized, activated and analyzed using GC, FESEM, BET, DTA-TGA, XRF and FTIR analysis. The activated Paphia undulata shells waste (APSW) had a maximum surface area of 2.1290 m 2/g, diameters of 17- 3000 Å, pores adsorption and desorption cumulative volume were 0.006841cm 3/g and 0.006928cm 3/g with the pores size of 312.527 Å, and it reflected the composition of 83.99 – 86.25 % calcium oxide, etc. The resulted Rubber and Jatropha seeds oil biodiesel yields of 75.93% and 93.33% were found by the methanol/oil ratio of 6:1, catalyst amount of 4 wt.%, temperature of 60oC and reaction time of 3 hours. The synthesized biodiesels were approved by GC-MS, and its properties fulfills the limitation of specification described by ASTM D6751.